ANALISIS SOSIOLINGUISTIK MEIREI HYOUGEN DALAM ANIME MOBILE SUIT GUNDAM IRON-BLOODED ORPHANS KARYA TATSUYUKI NAGAI - Wulandari, Retno; Rahmalina, Reny (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2024)
Based Yokata (2007:140) meirei hyougen is when the speaker wishing an action or condition from listener.This study discusses the form and use of meirei hyougen related to speech acts contained in the anime Mobile Suit Gundam Iron Blooded Orphans in the second series of episodes 15-20. This research belongs to the type of qualitative research with descriptive qualitative method. The data in this study are conversations of characters containing meirei hyougen in the Mobile Suit Gundam Iron Blooded Orphans anime, the data source in this study is the Mobile Suit Gundam Iron Blooded Orphans anime in the second series of episodes 15-20. The instrument in this research is the researcher himself. in this study 66 meirei hyougen data were found, namely; 33 using verbs and command forms, 1 form (o~ kudasai), 1 form (~meizaru), 24 descriptive forms, and 7 forms (~kudasai, ~tekure, o~negaimasu from irai hyougen). But, there are also those that are not found namely; form (~nasai), form (~koto/~youni), form (~tamae). After finding the formation of meirei hyougen, we also found the factors behind its use through SPAKING theory. From 66 data, the factors that cause the use of meirei hyougen using SPEAKING theory are analyzed, including Setting/Scene, Participant, Ends, Act, Key, Instrumentalities, Norm and Genre.